The Development of Elderly Well-Being Based on Buddhist Ethics at Wat Sai Thong, Nong Wa Subdistrict, Mueang District, Nong Bua Lamphu Province - Thawarathammo (Namdee), Phramaha Thamaphat; Thongpan, Suwin (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were: 1) to investigate the conditions of the elderly at Saithong Temple, Nong Wa Subdistrict, Mueang District, Nong Bua Lamphu Province; 2) to study the Buddhist ethical principles used to promote happiness among the elderly; and 3) to develop a model for enhancing the happiness of the elderly based on Buddhist ethics at Saithong Temple. This study employed a qualitative research methodology. Research instruments included in-depth interviews and behavioral observation forms. Key informants consisted of 5 monks, 15 elderly persons, and 5 healthcare personnel. Data were analyzed using descriptive analysis. The findings revealed that: 1) the conditions of the elderly at Saithong Temple comprised three aspects: (1) age-related changes in four dimensions, namely physical, mental, social, and intellectual; (2) problems encountered by the elderly in the same four dimensions; and (3) needs of the elderly in three areas, including basic necessities, safety, and social esteem. 2) The Buddhist ethical principles used to promote happiness among the elderly consisted of four dimensions: physical health care, including Kyabhvan (physical development), Sappyakr, Sappye Mattaññut, Patabhog, and Klacr; mental health care, including Cittabhvan (mental development) and Brahmacariya; social well-being, including Slabhvan (moral development) and Sagahavatthu IV (the Four Bases of Social Solidarity); and intellectual development, including Paññbhvan (wisdom development) and Brahmavihra IV (the Four Sublime States of Mind). 3) The development process for enhancing elderly happiness based on Buddhist ethics was implemented through four activities: paying homage to the Buddha, observing the Five Precepts and offering alms; chanting and performing daily prayers; listening to Dhamma sermons; and practicing meditation with loving-kindness. The outcomes indicated that the elderly demonstrated better physical self-care and understanding of age-related changes, stronger mental resilience and emotional control, peaceful coexistence within society, and improved ability to solve problems rationally through wisdom.